Analisis Rasio Profitabilitas Dalam Mengukur Kinerja Keuangan PT POS IND Logistik (2018-2023) Dengan Pendekatan NVIVO 12 - Hafizah Sri Rahma Wulandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study was to determine whether the financial performance of PT Pos Ind Logistik Indonesia has been carried out well or not against its financial performance as measured by the profitability ratio approach. In this study, the author made PT Pos IND Logistik Indonesia the object of research. The data collection method in this study used documentation techniques. The data obtained consisted of the financial statements of PT Pos IND Logistik Indonesia for 2018-2023 through the website https://www.idx.co.id. The theory used in this study comes from various literature that is in accordance with the study to be studied, both from books and from others. This study uses a qualitative research method using primary data sources, namely financial reports. The data analysis method uses a comparative coding approach using coding application data, namely NVivo 12 Plus software. The results of this study are that the financial performance of PT Pos IND Logistik Indonesia for 2018-2023 is said to be not good enough. This is evidenced by the profitability ratio as measured by the Return on Assets value, the results of which are still less than 30% and Return on Equity is also still less than 40%. Meanwhile, the profitability ratio is seen with the Net Profit Margin, Gross Profit Margin, EBITDA Margin and Operating Profit Margin values ​​which have decreased until 2023.